CONTRIBUCIONES AL CONOCIMIENTO DE LOS MURCIELAGOS MEXICANOS IV - VILLA RAMIREZ, BERNARDO; MARTINEZ, LIBORIO (Rockefeller Foundation, CD MEXICO, DF, MEX, 1942)
Subgenus MICRODIAPTOMUS, and D cokeri, are described
ANS INST BIOL
Keywords: CONTRIBUCIONES, CONOCIMIENTO, MURCIELAGOS MEXICANOS IV; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; MAMIFEROS